Perancangan Identitas Visual UMKM Ecoprint Girly Lestari di Surabaya - Nabilah Charisma Azelia; Asidigisianti Surya Patria (Jurnal SASAK : Desain Visual dan Komunikasi, 2022)
Micro, Small, and Medium Enterprises (MSME) Ecoprint Girly Lestari is a small business that sells fashion and accessories products with ecoprint patterns. This MSME is one of the MSMEs that sells its products at the Surabaya Kriya Gallery. Established in 2019, Ecoprint Girly Lestari does not have a conceptual and consistent visual identity. It can be seen through the differences in logo usage in each media. This condition makes consumers difficult to recognize their products. Therefore, this study aims to describe the visual identity design process for Ecoprint Girly Lestari MSMEs. This research is qualitative with interview, observation, documentation, and literature study data collection techniques and uses the STP and the SWOT analysis methods. The result of visual identity design is a logo with a design concept that has been adapted to the uniqueness and target audience of MSMEs. The logo is applied to several media such as hang tags, clothing labels, paper sleeves, paper bags, business cards, neon box and stationary. There are also supporting media such as brochures and x-banners. Guidelines for logo usage are written in Graphic Standard Manual (GSM).